HUBUNGAN KEAKTIFAN BERTANYA DENGAN HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI IPS SMA - Hotijah, Siti; S, Bambang Genjik; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this study is to find out if there is a relationship the liveliness of asking students with class XI IPS learning outcomes at Taman Mulia High School District of Kubu Raya. The research method used is correlational with quantitative research. The sample in this study amounted to 32 students of class XI IPS. The collection method is done by observation, interview, and documentation. Descriptive statistical test results on the liveliness of asking students showed an average of 85.87with a percentage of 58% as many as 32 students included in the high category. While the descriptive statistical test results of student learning outcomes showed an average of 86 with a percentage of 68% as many as 32 students included in the medium category. Where the results of testing the correlation coefficient hypothesis shows that there is a significant relationship between the liveliness of asking with student learning outcomes XI IPS class at Taman Mulia High School, Kubu Raya Regency. This is indicated by the r_count value of 0.89 which is classified into high correlation intervals. T value obtained is equal to t_count = 10,799 which is greater than t_table, so it can be concluded that there is a significant relationship between T value obtained is equal to t_count = 10,799 which is greater than t_table, so it can be concluded that there is a significant relationship between the liveliness of askingwith student learning outcomes class XI IPS SMAS Taman Mulia, Kubu Raya Regency. Keywords: Field Of Economic Studies, Learning Outcomes, The Liveliness Of Asking